AutoPVS1: An automatic classification tool for PVS1 interpretation of null variants. Issue 9 (29th June 2020) - Xiang, Jiale; Peng, Jiguang; Baxter, Samantha; Peng, Zhiyu
Abstract: Null variants are prevalent within the human genome, and their accurate interpretation is critical for clinical management. In 2018, the ClinGen Sequence Variant Interpretation (SVI) Working Group refined the only criterion with a very strong pathogenicity rating (PVS1). To streamline PVS1 interpretation, we have developed an automatic classification tool with a graphical user interface called AutoPVS1. The performance of AutoPVS1 was assessed using 56 variants manually curated by the ClinGen's SVI Working Group; it achieved an interpretation concordance of 93% (52/56). A further analysis of 28, 586 putative loss‐of‐function variants by AutoPVS1 demonstrated that at least 27.7% of them do not reach a very strong strength level, 17.5% because of variant‐specific issues and 10.2% due to disease mechanism considerations. Notably, 41.0% (1, 936/4, 717) of splicing variants were assigned a decreased preliminary PVS1 strength level, a significantly greater fraction than in frameshift variants (13.2%) and nonsense variants (10.8%). Our results reinforce the necessity of considering variant‐specific issues and disease mechanisms in variant interpretation and demonstrate that AutoPVS1 meets an urgent need by enabling biocurators to easily assign accurate, reliable and reproducible PVS1 strength levels in the process of variant interpretation. AutoPVS1 is publicly available at http://autopvs1.genetics.bgi.com/ . Abstract : Automatic PVS1 interpretation (AutoPVS1) is an automatic classification tool developed by BGI Genomics to support PVS1 interpretation of null variants. AutoPVS1 is based on the recommendations outlined by ClinGen's SVI Working Group, which consists of two steps. The first step is to address variant specific issues; the second step is to consider disease mechanisms. AutoPVS1 defines the results of the first step as "preliminary PVS1 strength" and the results of the second step as "adjusted PVS1 strength"